THE EFFECT OF INCUBATION TIME AND LEVEL OF UREA ON DRY MATTER, ORGANIC MATTER AND CRUDE PROTEIN DIGESTIBILITY OF PASSION FRUIT (Passiflora edulis var. flavicarpa) HULLS - Astuti, T.; Warly, L.; Jamarun, N.; Evitayani, E. (Journal of the Indonesian Tropical Animal Agriculture, 2011)
This research was aimed to evaluate the effect of incubation time and level of urea on dry matter,organic matter and crude protein digestibility of Passion fruit hulls. The research was conducted by twophases. The first, the research was conducted to analyze of Passion fruit hulls before and afterammoniation, and then conducting digestibility of Passion fruit hulls using rumen fluid. FactorialRandomized Block design 2x3, with factor A was incubation time of ammoniated Passion fruit hulls (2weeks, 3 weeks) and factor B was the level of urea used (4%, 6% and 8%) was used in this study. Theresults showed that there was no significantly effects among treatments on dry matter and organic matterdigestibilities, but significant effect (P<0.05) on crude protein digestibility by level of urea treatment,even those there was no interaction between each treatment. The research showed that increasing levelof urea could increase in-vitro digestibility of crude protein nutrients. In conclusion, the best treatmentwas 8% level of urea with 2 weeks of incubation length.